Determination of the cell-free layer in circular PDMS microchannels - Cerdeira, Tânia Filipa Alves (2010)
In microcirculation the cell-free layer is believed to reduce the friction between red blood cells (RBCs) and endothelial cells and consequently reduce blood flow resistance. However, the complex formation of the cell-free layer has not yet been convincingly described mainly due to multi-physical and hemorheological factors that affect this phenomenon. In this experimental work, we study the effect of hematocrit (Hct) on the thickness of the cell-free layer in straight circular polydimethylsiloxane (PDMS) microchannels. The channels studied are 73 ± 2 mm in diameter, flexible and circular to mimic blood vessels. The images are captured using confocal microscopy and are post-processed using Image J and MATLAB. The formation of a cell-free layer is clearly visible in the images captured and by using a combination of image analysis techniques we are able to detect an increase in the cell-free layer thickness as Hct decreases.